Walnuts and almonds as model systems of foods constituted by oxidisable, pro-oxidant and antioxidant factors - Salcedo, Cecilia Luciana (2010)
Walnuts and almonds were selected as complex model systems in order to study possible interactions among oxidisable substances, pro-oxidant species and antioxidants. Lipoxygenase activities in a direct-micelle system were determined for these nuts according their globulin contents in their soluble protein fraction. Walnut lipoxygenase activity was 1.5 times higher than that of almonds. Among antioxidant compounds, hydrophilic contents were analysed in these nuts, hence, extractable, hydrolysable and condensed phenolic compound fractions were determined as well as lipophilic phenolic concentration corresponding to tocopherol fraction. Extracts of brown skins and whole walnuts have significantly higher phenolic contents than those of almonds. Radical scavenging activities of phenolic extracts were measured. Besides, the experiments demonstrated the ability of all nut extracts to inhibit the coupled oxidation of linoleic acid with β-carotene induced by lipoxygenase. The antioxidant substances were mainly found in nut brown skins. Walnut extracts showed higher antioxidant activity than those of almonds. Lipoxygenase pro-oxidant activity was also measured in AOT reverse micelles in conditions that model these nuts.